Solvability of a Class of N -th Order Linear Focal Problems - Almenar, Pedro; Jodar, Lucas (Mathematical Modelling and Analysis, 2017)
This paper presents a recursive method which yields necessary and sufficient conditions for the existence of solutions of a class of n-th order linear focal boundary value problems in the interior of a given interval, in the form of integral inequalities. Some results on the sign of the derivatives of the Green functions of n-th order linear focal boundary value problems will also be provided.